STUDIES ON PHYTOCHEMICAL CONSTITUENTS, ANTIMICROBIAL AND ANTIOXIDANT ACTIVITIES OF SOME MEDICINAL PLANTS OF NORTH COASTAL ANDHRA PRADESH - MAHESH KUMAR MVS; VSSL PRASAD TALLURI; S V RAJAGOPAL (International Journal of Pharma and Bio Sciences, 2014)
The phytochemical, antimicrobial activity against gram negative and positive bacteria and fungi, DPPH radical scavenging and FRAP assay antioxidant activities of aqueous and organic crude extracts of Millingtonia hortensis, Andrographis paniculata, Aegle marmelos, Coccinia grandis, Tinospora cordifolia, Achyranthus aspera was studied invitro. The phytochemical screening of crude plant extracts revealed the presence of bioactive compounds such as phenols, flavanoids, alkaloids, terpenoids, glycosides, phytosterols and proteins. All the extracts exhibited antibacterial and antioxidant activities and the activities varied from solvent to solvent. The results showed that methanlolic extracts exhibited significant antimicrobial and antioxidant activities when compared to other organic solvent and aqueous extracts. Further, the crude methanolic extract of Millingtonia hortensis exhibited significant activities when compared to the crude methanolic extracts of other plants.